Effectiveness of Early Psychosis Intervention: Comparison of Service Users and Nonusers in Population-Based Health Administrative Data - Anderson, Kelly K; Norman, Ross; MacDougall, Arlene; Edwards, Jordan; Palaniyappan, Lena; Lau, Cindy; Kurdyak, Paul (The American journal of psychiatry, 2018)
Objective:Early psychosis intervention (EPI) programs improve clinical and functional outcomes for people with first-episode psychosis. Less is known about the impact of these programs on the larger health care system. The authors sought to compare indicators of health service use, self-harm, suicide, and mortality between people with first-episode psychosis who were using EPI services and a propensity-matched group of concurrent control subjects who were not accessing EPI services.Method:A retrospective cohort of incident cases of nonaffective psychosis in the catchment area of the Prevention and Early Intervention Program for Psychoses in London, Ontario, between 1997 and 2013 was constructed using health administrative data. This cohort was linked to primary data from the same program to identify people who used EPI services. Outcomes for people who used EPI services and those who did not were compared using Cox proportional hazards models.Results:People who used EPI services had substantially lower rates of all-cause mortality in the 2-year period after EPI program admission (hazard ratio=0.24, 95% CI=0.11–0.53), although a significant difference in self-harm (hazard ratio=0.86, 95% CI=0.18–4.24) and suicide (hazard ratio=0.73, 95% CI=0.29–1.80) between the two groups was not observed. Those who used EPI services also had lower rates of emergency department presentation (hazard ratio=0.71, 95% CI=0.60–0.83) but higher rates of hospitalization (hazard ratio=1.42, 95% CI=1.18–1.71). These benefits were not observed after 2 years, when EPI care is typically stepped down to medical management.Conclusions:People with first-episode psychosis who used EPI services had mortality rates that were four times lower than those with first-episode psychosis who did not use these services, as well as better outcomes across several health care system indicators. These findings support the effectiveness of EPI services for the treatment of first-episode psychosis in the larger context of the overall health care system.